2015
DOI: 10.1088/0004-637x/812/2/171
|View full text |Cite
|
Sign up to set email alerts
|

Seed Population in Large Solar Energetic Particle Events and the Twin-Cme Scenario

Abstract: It has been recently suggested that large solar energetic particle (SEP) events are often caused by twin CMEs. In the twin-CME scenario, the preceding CME is to provide both an enhanced turbulence level and enhanced seed population at the main CME-driven shock. In this work, we study the effect of the preceding CMEs on the seed population. We examine event-integrated abundance of iron to oxygen ratio (Fe/O) at energies above 25 MeV/nuc for large SEP events in solar cycle 23. We find that the Fe/O ratio (normal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…We suggest that another key factor is the non-linear nature of CME-shock acceleration. It has been claimed that the largest SEP events occur when a fast CME follows on the heels of an earlier one from the same active region [19,20]. Although there may also be other factors at play, the seed particles generated by the first CME-shock provide a natural means of improving the acceleration efficiency at the second shock.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that another key factor is the non-linear nature of CME-shock acceleration. It has been claimed that the largest SEP events occur when a fast CME follows on the heels of an earlier one from the same active region [19,20]. Although there may also be other factors at play, the seed particles generated by the first CME-shock provide a natural means of improving the acceleration efficiency at the second shock.…”
Section: Discussionmentioning
confidence: 99%
“…If suprathermal electrons are accelerated by ICME shocks in the corona in a similar manner to suprathermal ions (e.g. Kahler and Vourlidas, 2014;Ding et al, 2015), then this would represent a severe deviation from the scenario described in Sect. 1.…”
Section: Icme Effects On Suprathermal Electronsmentioning
confidence: 98%
“…Only half of the events were associated with meter wavelength type III radio bursts. Furthermore, many authors suggested that the ambient suprathermal seed particles from the previous solar flares [54] [12] [16] and from the preceding CMEs [23] [48] [16] [45] [58] can play an important role for producing the large SEP events.…”
Section: Introductionmentioning
confidence: 99%